SYNTHESIS AND CHARACTERIZATION OF OXIDE SUPPORTED MONOMETALLIC Fe AND Cu CATALYSTS FOR STEAM GASIFICATION OF PKS TO HYDROGEN - MOHAMAD, MAS FATIHA (2015)
Biohydrogen is a renewable source of clean fuel and energy which can be derived from biomass. One of the suitable candidate as a source of biomass is palm kernel shell (PKS). An effective approach to produce hydrogen rich gas is via catalytic gasification as the catalyst may promote high content of product gases and eliminate tar. The potential of using Ceria (Ce02) and Titania (TiOi) supported catalysts for the production of biohydrogen from PKS were explored using Fe and Cu as the active metals with 2.5, 5, 7.5 and 10 wt% metal loading. The catalysts were prepared by incipient wetness impregnation method for 4 hours, dried at 120°C and calcined P+ ^flO °C for 16 h The nhvcicrichernieal nrrvnerties nf these catalvsts were characterized using XRD, N2 adsorption-desorption isotherm, TPR and FESEM. Catalysts screening was performed in dry PKS gasificationusing Temperature Programmed Gasification (TPG) system at temperature range of100 - 700 °C in 5% 02/He ata flow rate of 10 ml min"1 with PKS weight of 0.3 g and PKS to catalyst ratio of 3. The gaseous products formed namely H2, CO2, CO and CH4 were detected by mass spectrometer, following its m/z = 2, 44, 28, and 16 respectively.